2020
DOI: 10.5603/gp.a2020.0127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on pregnancy and delivery — current knowledge

Abstract: The World Health Organization announced on 12 March 2020 a global pandemic of the new SARS-CoV-2 coronavirus causing COVID-19 disease associated with pneumonia and acute respiratory failure. SARS-CoV-2 has caused so far over 6.66 million recorded cases, of which 393,000 ended in death (as of June 1, 2020). Despite the demographic statistics of incidence, there is no current recording of cases in the group of pregnant or perinatal women. Changes occurring in the female body system during pregnancy also affect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Moreover, the reduction of the innate immune responses in pregnant women increased maternal susceptibility to COVID-19 infection that involved high maternal mortality [ 61 , 62 ], which may lead to maternal anxiety and depression symptoms. In addition, pregnant women faced many difficulties during the COVID-19 pandemic, such as limitation in assessing healthcare services [ 5 ] and the chance of infection during delivery and hospital visits [ 63 ], especially the high risk of delivery in the late pregnancy, which may increase the possibility of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduction of the innate immune responses in pregnant women increased maternal susceptibility to COVID-19 infection that involved high maternal mortality [ 61 , 62 ], which may lead to maternal anxiety and depression symptoms. In addition, pregnant women faced many difficulties during the COVID-19 pandemic, such as limitation in assessing healthcare services [ 5 ] and the chance of infection during delivery and hospital visits [ 63 ], especially the high risk of delivery in the late pregnancy, which may increase the possibility of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Available recommendations regarding the week of delivery in women with confirmed or suspected COVID-19 infection are limited. Only five publications recommended considering delaying the delivery date, but only if maternal and fetal conditions permitted [ 25 , 27 , 45 , 47 , 49 ]. On the other hand, only one publication indicated that COVID-19 is not an indication for preterm delivery [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining recommendations, 6 made at the non-country specific level [ 25 , 26 , 36 , 38 , 39 , 56 ] and 11 at the national level [ 29 , 30 , 42 , 44 , 45 , 47 , 48 , 52 , 53 , 57 , 58 ], allowed for family births with 1 person arranged by the mother. Making the possibility of family birth dependent on local conditions and leaving the final decision to the authorities of each hospital were included in four papers, one on the non-country specific level [ 49 ] and three on the national level [ 23 , 24 , 53 ]. Moreover, one paper recommended no visitors or one support person [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations